Pengaruh Metode Discovery Learning Terhadap Kemampuan Mengenal Warna pada Anak Usia 4-5 Tahun Di TK Negeri 04 Sambelia - Tina Ayu Miranda; Gunawan; Baik Nilawati Astini (Syntax Corporation Indonesia, 2023)
This research aims to determine the effect of the discovery learning method on color abilities in children aged 4 - 5 years old at TK Negeri 04 Sambelia. This type of research uses quantitative methods with pre-experimental research type one group pretest-posttest design. This research was carried out in four treatments. In each treatment there are stages, namely planning, implementation and evaluation. The subject of this research is group A2 of Kindergarten 04 Sambelia. The instrument used was a checklist sheet with observation data collection techniques. The use of the discovery learning method is able to improve children's cognitive abilities in recognizing colors in class A2 at TK Negeri 04 Sambelia. The child's ability to name, convey and group things as a form of recognition of colors increases with each treatment. The results of the research in the t value table at the 5% significance level are 2.27. It is known that to is 20.95 > 2.27. Because to is greater than tt, the proposed hypothesis (ho) is rejected and the alternative hypothesis is accepted (ha). This research shows that there is an influence of the discovery learning method on the ability to recognize colors in children aged 4-5 years at TK Negeri 04 Sambelia.